Modeling the climate response to a massive methane release from gas hydrates - Renssen, H.; Beets, C.J.; Fichefet, T.; Goosse, H.; Kroon, D. (Paleoceanography, 2004)
The climate response to a massive release of methane from gas hydrates is simulated in two 2500-year-long numerical experiments performed with a three-dimensional, global coupled atmosphere-sea ice-ocean model of intermediate complexity. Two different equilibrium states were used as reference climates; the first state with preindustrial forcing conditions and the second state with a four times higher atmospheric CO